KIPRAH SYAIKH AL-ZAYTUN SEBAGAI PENJAGA KEBERAGAMAN MELALUI LEMBAGA PENDIDIKAN AL-ZAYTUN YANG MEMILIKI VISI DAN MISI PUSAT PENDIDIKAN PENGEMBANGAN BUDAYA TOLERANSI DAN PERDAMAIAN - Haritsah, Haritsah; Nur Sidiq Al Fath, Imam; Ngainnur Rohmah, Siti (Tashdiq: Jurnal Kajian Agama dan Dakwah, 2024)
Tolerance is an attitude of respecting differences in beliefs, cultures, and traditions, which serves as an essential foundation for fostering social harmony and religious coexistence. Indonesia, as a nation rich in ethnic, religious, and cultural diversity, regards tolerance as vital to maintaining unity and preventing interfaith conflicts. This study aims to understand and explain the significance of tolerance in fostering interfaith harmony within diverse societies, particularly in Indonesia. The research method employed is a literature review using a descriptive analytical approach. The findings reveal that tolerance involves not only passive acceptance of differences but also active interaction that supports harmonious relationships. Education plays a crucial role in instilling the values of tolerance from an early age, as exemplified by Al-Zaytun through its approach of role modeling and habituation. However, the challenges of intolerance, often driven by prejudice and a lack of understanding, must be addressed through dialogue, collaboration, and the reinforcement of universal human values. Thus, tolerance serves as a cornerstone for building peace and social stability in pluralistic societies while strengthening unity in diversity. Keywords: Diversity, Tolerance, Ma’had Al-Zaytun, Peace